Aplikasi Bimbingan Belajar Siswa Sekolah Menengah Pertama Negeri 1 Tana Righu dengan Metode Object-Oriented Technology - Sartini Poety; Gergorius Kopong Pati; Lidia Lali Momo (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
The rapid development of information technology has created significant opportunities for secondary schools to improve the quality of learning through the use of digital-based applications. This study aims to design and develop a web-based tutoring application for students of Junior High School (SMP) Negeri 1 Tana Righu by applying Object Oriented Technology (OOT) as the software development approach. OOT was chosen for its ability to simplify the system design process through structured modeling using the concepts of classes, objects, attributes, and relationships between objects. The developed application provides various features, including the presentation of learning materials, interactive practice questions, learning outcome evaluations, and student progress reports accessible in real time by both teachers and students. The research method consisted of needs analysis, system design using UML diagrams, implementation, and application testing. The testing results indicate that the tutoring application is effective in improving the learning process, assisting teachers in monitoring and evaluating student progress, and providing students with a more engaging and interactive learning experience. Therefore, this application is expected to serve as an innovative solution to support tutoring activities in secondary schools and contribute positively to enhancing the quality of education in the digital era.